Detection of a tadalafil analogue as an adulterant in a dietary supplement for erectile dysfunction - Ulloa, Jerónimo Luis (2014)
INTRODUCTION: Several cases of adulteration of dietary supplements with tadalafil, sildenafil, and vardenafil, or their unapproved analogues have been reported worldwide. Mainly, the presence of the latter represents a serious health risk to consumers as their efficacy and toxic effects have not been assessed and may result in unpredictable adverse effects. AIM: To investigate the suspected adulteration with synthetic phosphodiesterase type 5 (PDE-5) inhibitors in a dietary supplement marketed in Argentina for the treatment of erectile dysfunction (ED). METHODS: The content of the capsules of the dietary supplement (sample A) was analyzed by thin layer chromatography (TLC) and high-performance liquid chromatography (HPLC) diode-array detection. From the organic extract of sample A, a major compound was purified by column chromatography (CC). The isolated compound was identified by proton nuclear magnetic resonance (1H NMR) and carbon NMR (13C NMR), heteronuclear single quantum coherence, distortionless enhancement by polarization transfer (DEPT 135), electrospray ionization mass spectrometry, and ultraviolet, and infrared (Fourier transform infrared spectroscopy) spectroscopy. MAIN OUTCOME MEASURE: Proof of adulteration of herbal products with synthetic PDE-5 inhibitors. RESULTS: By TLC and HPLC analysis, a major compound was detected in sample A organic extract. The purification of this extract by CC led to the isolation of a pure compound which was identified according to its spectral data as (6R,12aR)-2-amino-6-(1,3-benzodioxol-5-yl)-2,3,6,7,12,12a-hexahydropyrazino [1',2':1,6] pyrido [3,4-b] indole-1,4-dione or aminotadalafil. CONCLUSIONS: An unapproved PDE-5 inhibitor analogue, which was identified as aminotadalafil, has been detected in a dietary supplement. This study represents the first report in Latin America and one of the few independent studies of an adulteration with an unapproved PDE-5 inhibitor of an herbal product for ED treatment.